Peningkatan Literasi Membaca Melalui Penerapan Metode Membaca Kontesktual Pada Siswa Kelas X1 SMA Negeri 2 Kota Kupang Tahun Pelajaran 2024/2025: Indonesia - Feby Meriyana Atto; Sanhedri Boimau; Richard Oematan (Universitas Persatuan Guru 1945 NTT, 2026)
This study aims to determine the improvement of reading literacy through the application of contextual reading methods in class X1 students of SMA Negeri 2 Kota Kupang in the 2024/2025 academic year. This type of research uses classroom action research (PTK), by going through several stages, namely: planning, implementation, observation and reflection. The subjects of this study were 30 students of class X1 SMA Negeri 2 Kota Kupang. Data were collected using observation, test and documentation techniques. The results of this study showed that out of 30 students in Cycle I and Cycle II that the application of contextual reading methods can improve students' reading literacy.